Projected ENSO Teleconnection Changes in CMIP6. Issue 11 (31st May 2022) - McGregor, Shayne; Cassou, Christophe; Kosaka, Yu; Phillips, Adam S.
Abstract: The El Nino–Southern Oscillation (ENSO) has far reaching impacts through atmospheric teleconnections, which make it a prominent driver of global interannual climate variability. As such, whether and how these teleconnections may change due to projected future climate change remains is a topic of high societal relevance. Here, ENSO Surface Temperature (TAS) and Precipitation (PR) teleconnections between the historical and high‐emission future simulations are compared in more than 31 models from Phase 6 of the Coupled Model Intercomparison Project. We find significant future (2081–2100) TAS and PR teleconnection changes over approximately 50% of teleconnected regions in December‐February relative to 1950–2014. The large majority of these significant teleconnection changes suggest that an amplification of the historical teleconnections will occur, however, some regions also display a significant teleconnection dampening. Further to this, in many regions these ENSO teleconnection changes scale with the projected warming level, with higher warming leading to larger teleconnection changes. Plain Language Summary: The El Nino–Southern Oscillation (ENSO) has far reaching impacts through atmospheric teleconnections, which make it a prominent driver of global interannual climate variability. As such, whether and how these teleconnections may change due to projected future climate change remains a topic of high societal relevance. Here, ENSO surface temperature (TAS) and precipitation (PR) teleconnections between the historical and high‐emission future simulations from Phase 6 of the Coupled Model Intercomparison Project are compared. Focusing on the season when ENSO typically peaks (December‐February), we find significant future (2081–2100) TAS and PR teleconnection changes over approximately half of teleconnected regions relative to 1950–2014. The large majority of these significant teleconnection changes suggest that an amplification of the historical teleconnections will occur, however, some regions also display a significant teleconnection dampening. Further to this, in many regions these ENSO teleconnection changes scale with the projected warming level. This scaling of teleconnection changes with warming suggests that a lot of the changes to ENSO teleconnections can be avoided by minimizing future warming, or vice versa, larger year to year TAS and PR variability due to ENSO is likely to be experienced with strong future warming. Key Points: El Nino–Southern Oscillation (ENSO) teleconnection changes are found over ∼50% of teleconnected regions in December‐February for the period 2081–2100, relative to 1950–2014 The large majority of these projected teleconnection changes suggest that an amplification of the historical teleconnections will occur ENSO teleconnection changes largely scale with the projected warming level (i.e., higher warming leads to larger teleconnection changes)